2019
DOI: 10.1002/ase.1881
|View full text |Cite
|
Sign up to set email alerts
|

The Superficial Face Dissection as an Example for Integrating Clinical Approaches, Authentic Learning, and Changing Perspectives in Anatomy Dissection

Abstract: Hands‐on dissection‐based learning of anatomy offers an unique and valued experience for medical students. Too often however, the inexperienced student's focus is to avoid damage to unfamiliar structures instead of understanding spatial relationships between structures. This results in unfortunate surrender of a critical learning experience. Additionally, approaches to dissection and anatomic exposure share little alignment to clinical approaches, making it less powerful in clinical applicability. The goal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, some authors have stated its importance as a “rite of passage” (Dyer & Thorndike, 2000 ) or a “royal road” (Newell, 1995 ) and others that it is a form of learning that imparts more than just factual knowledge (Smith et al, 2020 ). Moreover, dissection itself is changing as it evolves to reflect the latest clinical practice (Cotofana & Lachman, 2020 ) and during the Covid‐19 pandemic, many educators have had to explore new ways for students to gain experience of human cadavers, for example, with material provided for asynchronous learning, to enable a stronger focus when students are in the anatomy laboratory (Smith and Pawlina, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have stated its importance as a “rite of passage” (Dyer & Thorndike, 2000 ) or a “royal road” (Newell, 1995 ) and others that it is a form of learning that imparts more than just factual knowledge (Smith et al, 2020 ). Moreover, dissection itself is changing as it evolves to reflect the latest clinical practice (Cotofana & Lachman, 2020 ) and during the Covid‐19 pandemic, many educators have had to explore new ways for students to gain experience of human cadavers, for example, with material provided for asynchronous learning, to enable a stronger focus when students are in the anatomy laboratory (Smith and Pawlina, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken into account the aforementioned, it is suggested that cadaveric dissections and prosections are performed with respect to standard surgical exposures and extending upward and downward. (Cotofana and Lachman, 2020). Since the technique of vascular exposures focuses on preserving major muscular structures, separate "vascular" dissections and prosections do not compromise the cadaver nor preclude studying of other anatomic systems with respect to classical dissection techniques.…”
Section: Suggestions For a Flexible And Applicable Vascular Anatomy T...mentioning
confidence: 99%
“…Most of the previous studies on authentic learning have focused on science, mathematics and language education (Akça & Ata, 2009;Aydın, 2019;Aynas, 2018;Bektaş & Horzum, 2014;Belaid & Murray, 2015;Belet, Boyacı, & Güner, 2017;Coşkun, Doğan, & Ulua, 2017;Cotofana & Lachman, 2020;Dadlı, 2017;Dennis & O'Hair, 2010;Dolapçıoğlu, 2015;Finch & Jefferson, 2013;Flanagan, 2014;Gençoğlan, 2017;Gregory, 2013;Gündoğan & Gültekin, 2017;Hamurcu, 2016;Herrington & Oliver, 2000;Herrington, Reeves, & Oliver, 2014;Hürsen, 2016;Karakoç, 2016;Koçyiğit & Zembat, 2013;Motlhaka, 2014;Newmann & Wehlage, 1993;Preus, 2012;Rule, 2006;Safuan & Soh, 2013;SAYE the Social Studies Inquiry Research Collaborative, 2013;Weninger, 2018;Westberg & Leppien, 2018;Yanti & Mulyono, 2020). However, in Turkey, very few studies have been conducted in the field of social studies education (Baştürk, 2019;Gürgil, 2018;İneç, 2017;İneç & Akpınar, 2017;Karakuş, 2006;Önger, 2019).…”
Section: Figure 1 Theoretical Structure Of Authentic Learningmentioning
confidence: 99%